铁路轴承试验机主轴疲劳强度有限元分析 - 尚振国; 王华 (Jixie chuandong)
The failure breaking accident of three main shafts in a railway bearing tester is occurred continuously.The finite element model of the main shaft is built and the static stress distribution is gained in order to find the reason of main shaft fracture.The work condition of shaft rotating and force fixing is simulated with shaft fixing and force rotating according to the preset load.The fatigue strength based on the static stress is calculated by professional software FE-SAFE.It is indicated that the fatigue fracture is possibly occurred because the fatigue strength safety coefficient of the main shaft is less than 1.The statics analysis and fatigue analysis of improved main shaft is executed complying with the same flow process as above mentioned.The result presents that the fatigue strength safety coefficient of the improved main shaft is 1.3 and is acceptable.